2000
DOI: 10.1523/jneurosci.20-16-05989.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Ets Transcription Factor GABP Is Required for Postsynaptic Differentiation In Vivo

Abstract: At chemical synapses, neurotransmitter receptors are concentrated in the postsynaptic membrane. During the development of the neuromuscular junction, motor neurons induce aggregation of acetylcholine receptors (AChRs) underneath the nerve terminal by the redistribution of existing AChRs and preferential transcription of the AChR subunit genes in subsynaptic myonuclei. Neural agrin, when expressed in nonsynaptic regions of muscle fibers in vivo, activates both mechanisms resulting in the assembly of a fully fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 65 publications
(75 reference statements)
5
46
0
1
Order By: Relevance
“…In agreement with previous reports, we show that the GABP complex is located exclusively in the nucleus (6,45). However, our in vitro approach with living C2C12 cells allowed us to determine that fluorescent GABP is entirely excluded from the nucleoli.…”
Section: Vol 23 2003 Phosphorylation-induced Changes Of Gabp 8015supporting
confidence: 92%
“…In agreement with previous reports, we show that the GABP complex is located exclusively in the nucleus (6,45). However, our in vitro approach with living C2C12 cells allowed us to determine that fluorescent GABP is entirely excluded from the nucleoli.…”
Section: Vol 23 2003 Phosphorylation-induced Changes Of Gabp 8015supporting
confidence: 92%
“…41 There is evidence that GABP functions as a transcriptional activator for synaptic genes, including nicotinic acetylcholine receptor, acetylcholine esterase and utrophin. 42,43 Thus, downregulation of the GABPA gene in skeletal myocytes after long-term exposure to Dex, as shown in our study, may indirectly reduce the transcription rate of these synaptic genes, potentially interfering with the nerve influx to the muscle. This hypothesis remains to be tested.…”
supporting
confidence: 55%
“…NRG-1 is sufficient to induce transcript levels of many NMJ genes, although recent reports showed that NRG-1 signaling is not required for NMJ formation in vivo (Escher et al 2005;Jaworski and Burden 2006). Importantly, agrin and NRG-1 signaling both converge on the transcription factor GABP (Briguet and Ruegg 2000). The two GABP subunits, GABPA and GABPB, are subsequently phosphorylated and bind to N-box elements in the promoters of NMJ genes.…”
Section: Pgc-1␣ Regulates the Nmj Gene Program Genes And Development 779mentioning
confidence: 99%